Dinamika China, ASEAN dan Indonesia - Herdi Sahrasad (Budapest International Research and Critics University, 2017)
That article said that the 21st century is a century belonging to Asia,especially China. By 2050 half the world's gross national product will bedominated by Asia where China is predicted to displace the US to secondplace and will be the world's strongest player, followed by India in third.Globalization has opened up barriers and boundaries for the movement ofinformation, capital, goods, services, people, as well as state ideology andnationalism. Indonesia, which by Gunnar Myrdal called soft country, shouldrapidly improve itself to rise and compete in the era of globalization whereChina is increasingly dominant in competing against the US and its allies inAsia.